2021
DOI: 10.1177/15579883211008337
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Physical Activity Levels and Psychological Well-Being Among Male University Students in South East, Nigeria: A Cross-Sectional Study

Abstract: This study aimed to evaluate the associations between physical activity (PA) and psychological well-being (PWB) among male university students. An institutionally based cross-sectional study was completed by 243 young men aged 18–30 years in a Nigerian public university. PA was measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), and PWB was measured by Ryff’s Scale of Psychological Well-being (PWB). The mean age of the participants was 24.9 ( SD = 7.61) and majority (39.1%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 78 publications
(99 reference statements)
4
11
0
Order By: Relevance
“…More specifically, significant differences were observed at the level of intrinsic motivation between the groups with different levels of physical activity, while at the level of extrinsic motivation these differences were only observed between the group with high levels of activity and the rest. These data agree with various studies [ 41 , 51 , 52 , 53 ] that show that physical activity is related to the most self-determined types of motivation, in addition to showing a slight influence of extrinsic motivation when the activity is vigorous. González–Hernández et al [ 54 ] report that people perform physical exercise because they are motivated by internal elements, such as feeling pleasure, escaping or feeling competent, and by external elements, such as being strong and, above all, interacting with other people and having fun.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…More specifically, significant differences were observed at the level of intrinsic motivation between the groups with different levels of physical activity, while at the level of extrinsic motivation these differences were only observed between the group with high levels of activity and the rest. These data agree with various studies [ 41 , 51 , 52 , 53 ] that show that physical activity is related to the most self-determined types of motivation, in addition to showing a slight influence of extrinsic motivation when the activity is vigorous. González–Hernández et al [ 54 ] report that people perform physical exercise because they are motivated by internal elements, such as feeling pleasure, escaping or feeling competent, and by external elements, such as being strong and, above all, interacting with other people and having fun.…”
Section: Discussionsupporting
confidence: 92%
“…In relation to these data, the linear regression model showed that intrinsic motivation was the most determining factor in predicting the level of physical activity, acquiring greater weight among men. This model agrees with other works [ 41 , 47 , 55 ] that discovered that men exercise to improve their self-image, with the aim of fulfilling a life purpose and overcoming challenges, which are characteristic elements of intrinsic motivation. However, women are motivated by factors such as improving their physical condition, losing weight, or reducing body fat, basing their motivation on elements that are external to the person [ 47 , 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations